REVIEW ON TITANIUM-BASED ALLOYS AS BIOMATERIALS FOR IMPLANT APPLICATIONS - Prastyo, Adi; Ibrahim, Fauzi; Efriyo Hadi, Agung; Febrina, Rina; Winarno, Rudi; Ermasari, Anissa; Wahyudi, Retno (Fakultas Teknik Universitas Malahayati, 2023)
ABSTRACT Technological updates in the field of advanced materials research now tend to focus on biomedical materials application and utilization of Titanium and its alloys. Various of implant materials have been employed in various disciplines of medical science depending on the requirements of a particular application. Metals, alloys, ceramics, and polymers are the commonly used biomaterials. Titanium and its alloys are commonly used in almost all disciplines of medicine because of their sufficient biocompatibility and meeting of mechanical requirements. The main focus of this study is to review the various structural and microstructural properties of titanium and titanium-based alloys used as orthopedic implants. Orthopedic implants need to possess certain important qualities to ensure their safe and effective use. These properties like the biocompatibility, relevant mechanical properties, high corrosion and wear resistance and osseointegration are summarized in this review. Various attempts to improve upon these properties like different processing routes, surface modifications have also been inculcated in the paper to provide an insight into the extent of research and benefit that has been put into developing a highly superior titanium orthopedic implant. In addition, this paper also discusses in detail the various surface modiﬁcation techniques to achieve superior biocompatibility, higher wear and corrosion resistance. Overall, an attempt has been made to bring out the current scenario of Ti based materials for biomedical applications. Keywords: titanium, implant, biomaterial.